Expert council resolution on regional program of early T2D detection, prevention and treatment in Russian Federation - Marina V. Shestakova; Oksana M. Drapkina; Sergey A. Boitsov; Luybov Y. Drozdova; Aleksander Y. Mayorov; Gagik R. Galstyan; Olga Y. Sukhareva (Сахарный диабет)
Type 2 diabetes prevalence is growing in Russia and worldwide. To date disease is considered as the leading cause ofmortality in many countries. To date, there is a need to develop integrated program of type 2 diabetes and prediabetes early detection and care. Within Advisory council experts developed recommendations regarding program plan including activities on type 2 diabetes early screening, prevention and care. The Public Screening Program for Adult Population is currently being implemented in Russia and should be considered as a background for activities on type 2 diabetes early prevention.